The priming effect and its impact on sport performance and difficulty judgment: evidence from Olympic bouldering - Medernach, J. P.; Aleithe, P.; Sanchez, X.; Memmert, D.; Henz, J. (Psychology of Sport and Exercise, 2026)
Introduction Priming refers to the psychological phenomenon whereby a prior stimulus modulates cognitive processes and behavioural responses. To date, perceptual-cognitive mechanisms through which priming influences sporting performance remain underexplored. Olympic Bouldering provides a compelling and ecologically valid context for investigating psychological priming, as it involves perceptual-cognitive processes sensitive to priming while offering robust performance indicators and a controllable experimental environment. This study aimed to advance theoretical and empirical understanding of psychological priming by examining the impact of manipulated difficulty labels, assigned to boulders (short climbing routes) and serving as primes, on climbers` performance outcomes and their perceived difficulty judgments (targets).